Case Report: A Novel de novo Mutation in DNM1L Presenting With Developmental Delay, Ataxia, and Peripheral Neuropathy - Wei, Yanping; Qian, Min (Frontiers in Pediatrics, 2021)
DNM1L encodes dynamin-related protein 1(DRP1), which is a member of the dynamin superfamily of GTPases and mediates mitochondrial and peroxisomal fission. In humans, several de novo heterozygous missense mutations in DNM1L have been reported, that was characterized by devastating courses with refractory epilepsy, myoclonus and brain atrophy on MRI. We describe a 4.5-year- old male child with a novel de novo mutation in DNM1L presenting an indolent phenotype of developmental delay, ataxia and peripheral neuropathy. The clinical features, magnetic resonance imaging findings and genetic results were summarized. Meanwhile, all the cases of DNM1L mutations reported were reviewed. DNM1L variants may need to be considered in a range of global developmental delay (GDD), peripheral neuropathy and ataxia.